2015
DOI: 10.1073/pnas.1403662111
|View full text |Cite
|
Sign up to set email alerts
|

Simple versus complex models of trait evolution and stasis as a response to environmental change

Abstract: Previous analyses of evolutionary patterns, or modes, in fossil lineages have focused overwhelmingly on three simple models: stasis, random walks, and directional evolution. Here we use likelihood methods to fit an expanded set of evolutionary models to a large compilation of ancestor-descendant series of populations from the fossil record. In addition to the standard three models, we assess more complex models with punctuations and shifts from one evolutionary mode to another. As in previous studies, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
177
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(183 citation statements)
references
References 54 publications
5
177
0
1
Order By: Relevance
“…Also, as noted elsewhere, we cannot yet discriminate whether turnover was driven by regional or global extinction, and in situ evolution or immigration, or the precise relative timings of these components. We note, however, that our findings may be consistent with recent models of evolution in response to fluctuating but trending global temperature change, which reproduce patterns of bounded trait evolution (stasis) on short time frames with pulses of accelerated evolutionary divergence at time spans of longer than a million years (36).…”
Section: Discussionsupporting
(Expert classified)
“…Also, as noted elsewhere, we cannot yet discriminate whether turnover was driven by regional or global extinction, and in situ evolution or immigration, or the precise relative timings of these components. We note, however, that our findings may be consistent with recent models of evolution in response to fluctuating but trending global temperature change, which reproduce patterns of bounded trait evolution (stasis) on short time frames with pulses of accelerated evolutionary divergence at time spans of longer than a million years (36).…”
Section: Discussionsupporting
(Expert classified)
“…We analyzed the temporal pattern of change in the standardized diversity curves using the maximum likelihood methods of Hunt et al (13). Models were fit that corresponded to stasis, directional change, unbiased random walk, an OU-OU process, as well as two-phase models incorporating a switch between simple models.…”
Section: Methodsmentioning
confidence: 99%
“…Model support was evaluated initially using AICc (Akaike information criterion with correction for finite sample size). Hunt et al (13) found that AICc tended to be overly liberal in favoring complex models and used parametric bootstrapping as a more conservative test of when complex models were favored over simple ones, an approach we follow here (SI Appendix, Maximum Likelihood Modeling).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fluctuating-RQH is associated with an oscillating mode of selection, where two antagonist species oscillate backwards and forwards between fitness optima, with one interactor always lagging behind the other [10]. This involves continual, yet non-directional, evolutionary motion for both antagonists, analogous to constrained stasis or a random walk in species morphology that produces no net change over the long term [29,30]. Finally, the Chase-RQH supposes that across the range of two interacting or co-evolving species, respective populations may be responding in different ways to the biotic milieu they experience [10].…”
Section: 'Down the Rabbit Hole' 1 : Introductionmentioning
confidence: 99%